Steatotic Hepatocytes Release Mature VLDL Through Methionine and Tyrosine Metabolism in a Keap1‐Nrf2–Dependent Manner. Issue 3 (15th September 2021) - Sano, Akitoshi; Kakazu, Eiji; Hamada, Shin; Inoue, Jun; Ninomiya, Masashi; Iwata, Tomoaki; Tsuruoka, Mio; Sato, Kosuke; Masamune, Atsushi
Abstract : Background and Aims: NAFLD is a lipotoxic disease wherein hepatic steatosis and oxidative stress are key pathogenic features. However, whether free amino acids (FAAs) are associated with the oxidative stress response against lipotoxicity has yet to be determined. We hypothesized that an imbalance of FAAs aggravates hepatic steatosis by interfering with the oxidative stress sensor. Approach and Results: C57BL/6 mouse immortalized hepatocytes, primary hepatocytes, and organoids were employed. Steatotic hepatocytes treated with oleic acid (OA) were cultured under FAA‐modifying media based on the concentrations of FAAs in the hepatic portal blood of wild‐type (WT) mice. As in vivo experiments, WT hepatocyte‐specific Kelch‐like ECH‐associated protein 1 ( Keap1 ) knockout mice (Keap1 ∆hepa ) and Cre‐ control mice (Keap1 fx/fx ) were fed high‐fat (HF) diets with modified amino acid content. The correlations were analyzed between the areas of lipid droplets (LDs) around central vein and plasma OA/FAA ratio in 61 patients with NAFLD. Mice fed an HF, Met‐restricted, and tyrosine (Tyr)‐deficient diet showed the NAFLD‐like phenotype in which the nuclear translocation of nuclear factor erythroid 2–related factor 2 (Nrf2), triglyceride‐rich VLDL, and fumarate were decreased in liver, but Keap1 ∆hepa ameliorated these phenomena. Reactive oxygen species and LDs induced by the deprivation of Met and Tyr were prevented in hepatic organoids generated from Keap1 ∆hepa . Dimethyl fumarate, an Nrf2 inducer, ameliorated the steatosis and increased the hepatic fumarate reduced by the deprivation of Met and Tyr in vitro . OA/Met or Tyr ratio in peripheral blood was associated with the hepatic steatosis in patients with NAFLD. Conclusions: An imbalance between free fatty acids and Met and Tyr induces hepatic steatosis by disturbing the VLDL assembling through the Keap1‐Nrf2 system.